High-Dose Clopidogrel in Patients with High Residual Reactivity: Results from the GRAVITAS Trial - Gordon, Debra (MD Conference Express, 2010)
Doubling the dose of clopidogrel in patients with high residual platelet activity after percutaneous intervention has no significant effect on cardiovascular outcomes, according to the neutral results of the Gauging Responsiveness with A VerifyNow Assay—Impact on Thrombosis And Safety [GRAVITAS; NCT00645918] trial.